Oral semaglutide versus injectable glucagon-like peptide-1 receptor agonists: a cost of control analysis. (2nd June 2020) - Hansen, B. B.; Nuhoho, S.; Ali, S. N.; Dang-Tan, T.; Valentine, W. J.; Malkin, S. J. P.; Hunt, B.
Abstract: Aims: The efficacy and safety of oral semaglutide, the first glucagon-like peptide-1 (GLP-1) receptor agonist developed for oral administration for the treatment of type 2 diabetes, was evaluated in the PIONEER clinical trial program, and a recently published network meta-analysis allowed comparison with further injectable GLP-1 receptor agonists. The present study aimed to assess the short-term cost- effectiveness of oral semaglutide 14 mg versus subcutaneous once-weekly dulaglutide 1.5 mg, once-weekly exenatide 2 mg, twice-daily exenatide 10 µg, once-daily liraglutide 1.8 mg, once-daily lixisenatide 20 µg, and once-weekly semaglutide 1 mg, in terms of the cost per patient achieving glycated hemoglobin (HbA1c) targets (cost of control). Materials and methods: Cost of control was calculated by dividing the annual treatment costs associated with an intervention by the proportion of patients achieving the treatment target with an intervention, with outcomes calculated for targets of HbA1c ≤6.5% and HbA1c <7.0% for all included GLP-1 receptor agonists. Annual treatment costs were accounted in 2019 United States dollars (USD), based on 2019 wholesale acquisition cost. Results: For the treatment target of HbA1c ≤6.5%, once-weekly semaglutide 1 mg and oral semaglutide 14 mg were associated with the lowest costs of control, at USD 15, 430 and USD 17, 383 per patient achieving target, respectively. Similarly, the cost of control was lowest with once-weekly semaglutide 1 mg at USD 12, 627 per patient achieving target, followed by oral semaglutide 14 mg at USD 13, 493 per patient achieving target for the target of HbA1c <7.0%. All other interventions were associated with higher cost of control values for both targets. Conclusions: Oral semaglutide 14 mg is likely to be cost-effective versus dulaglutide, exenatide (once weekly and twice daily), liraglutide, and lixisenatide in terms of bringing people with type 2 diabetes to glycemic control targets of HbA1c ≤6.5% and HbA1c <7.0% in the US.